2019
DOI: 10.1097/sla.0000000000003231
|View full text |Cite
|
Sign up to set email alerts
|

A National Analysis of Short-term Outcomes and Long-term Survival Following Thoracoscopic Versus Open Lobectomy for Clinical Stage II Non-Small-Cell Lung Cancer

Abstract: Objective: To compare outcomes after open versus thoracoscopic (VATS) lobectomy for clinical stage II (cN1) non-small-cell lung cancer (NSCLC). Background: There have been no published studies evaluating the impact of a VATS approach to lobectomy for N1 NSCLC on short-term outcomes and survival. Methods: Outcomes of patients with clinical T1-2, N1, M0 NSCLC who underwent lobectomy without induction therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…In contrast, similar postoperative complications were observed between converted and planned thoracotomy patients 20,21 . A recent study based on the National Cancer Database also reported similar complication rates and long-term survival between patients with planned and converted thoracotomy for clinical N1 disease 9 . In our study, the rate of thoracotomy conversion was 19% (23/121), and the rate of emergency cases due to vascular injury was 13.0% (3/23).…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, similar postoperative complications were observed between converted and planned thoracotomy patients 20,21 . A recent study based on the National Cancer Database also reported similar complication rates and long-term survival between patients with planned and converted thoracotomy for clinical N1 disease 9 . In our study, the rate of thoracotomy conversion was 19% (23/121), and the rate of emergency cases due to vascular injury was 13.0% (3/23).…”
Section: Discussionmentioning
confidence: 65%
“…Medbery et al [27] reported a lower rate of nodal upstaging with VATS than with open surgery (P < 0.001), but, in the subgroup of patients operated on in a university hospital, there was no difference between groups (P = 0.08). Recently, Yang et al [28] reported an absence of difference in the rate of nodal upstaging of patients with clinical T1-T2 N1 MO NSCLC and performed by VATS or open surgery (12% and 10.5%, respectively, P = 0.41). The five-year overall survival was not different between the two groups (48.6% and 48.7%, respectively, P = 0.76).…”
Section: Lymph Node Dissection and Nodal Upstaging By Rats Vats Andmentioning
confidence: 99%
“…A recent study of patients with cT1-2N1M0 NSCLC demonstrated that while VATS lobectomy was used in a minority of cases, there were no significant differences with regard to rates of nodal upstaging, 30-day mortality, or long-term survival. 44…”
Section: Oncologic Outcomes Of Vats Lobectomymentioning
confidence: 99%